Pengaruh Pendidikan dan Pelatihan terhadap Kinerja Pengurus PGRI Kabupaten Parigi Moutong dan Gurung Kidul - Rahmatiah Rahmatiah (Universitas Indraprasta PGRI Jakarta, 2018)
This study aimed to describe the effect of education and training on the performance of PGRI Board in Parigi Moutong and Gunung Kidul districts. The research question is how the influence of education and training on the performance of PGRI Board in Parigi Moutong and Gunung Kidul Districts? Data from this research are the mid-term report and end semester report form the districts about the progress of 5 aspects of organizational strengthening after training and also the data from PGRI's Membership Information System and Financial Information System. Data were analyzed with data in table form using descriptive-qualitative method. Based on the data analysis, PGRI board performance in both districts increased marked by the increase of 5 aspects of organizational strengthening after education and training. Another result is the PGRI board at the branch level in the two districts are motivated to improve organization.